Managing the NSW coastal zone: Restructuring governance for inclusive development. (1st December 2017) - Brooks, Kate; Fairfull, Sarah
Abstract: In 2013 the New South Wales (NSW) Government (Australia) established the NSW Marine Estate Management Authority (the Authority) to improve community engagement in coastal zone management. The outcome has been the coordination of activities and efforts of state government departments to maximize the social, economic and environmental values of the Marine Estate. While much has been written in regard to Integrated Coastal (Zone) Management (IC(Z)M) planning, papers that discuss its actual implementation are far fewer. This paper discusses how, given the minimal guiding literature in this area, the processes of IC(Z)M planning and implementation are being approached in NSW and its success to date. It is not a discussion of research undertaken, but a review and analysis of IC(Z)M in action, contextualized by a number of development approaches and theories that may help explain its emerging success in integrating government agency planning and activities. With reference to inclusive development and interactive governance theories, this paper discusses the principles and the five steps of the process adopted by the Authority. It reviews the challenges and achievements in developing appropriate and comprehensive consultation; threat and risk assessment procedures; and implementation and review processes. It concludes that the theory of inclusive development and interactive governance are well-founded and worthy aspirations in the IC(Z)M context. However, it also identifies that traditional governance frameworks of developed nation states, such as Australia, challenge the immediate and short term reality of achieving IC(Z)M. It identifies the key to success of IC(Z)M is the meta governance, expressed through the organizational culture of not only departments but their political masters, which need to be open, adaptive and flexible, and that this requires considerable focus as it remains an ongoing challenge. Highlights: This article describes the theories that contribute to implementing IC(Z)M from a governance and management perspective. It identifies three key outcomes from a case study of developing an integrated marine estate management plan. Identifies the necessity for effective governance to allow for coordinated (interactive) planning and action. Discusses management processes to address socially perceived and scientifically established threats to environmental assets. Resourcing of management development, implementation and monitoring is fundamental to successful, sustainable outcomes.